Educational utilization of virtual and mixed reality - Nam, SangHun (Edelweiss Applied Science and Technology, 2024)
This study investigated the application and acceptance of virtual reality (VR) and mixed reality (MR) technologies in university education. Here, university freshmen were introduced to these technologies and surveyed to assess their perceptions of VR and MR systems when applied in educational settings. The results demonstrate that the participants generally responded positively to both technologies, with VR being rated higher in terms of enjoyment and perceived usefulness. The findings suggest that students are more inclined to use VR in future educational settings. MR also received favorable evaluations; however, it received lower evaluations, particularly in terms of ease of use, which is likely due to the participants’ relative inexperience with the technology. The findings of this study highlight the potential of VR and MR technologies as effective educational tools and emphasize the importance of leveraging their respective advantages.